Noninvasive characterization of optical fibers - Schmidt, Soeren; Tiess, Tobias; Schroetter, Siegmund; Schwuchow, Anka; Jaeger, Matthias; Bartelt, Hartmut; Tuennermann, Andreas; Gross, Herbert (Optics Letters, 2017)
Capillary optical fibers with hole diameters of several micrometers are important for novel plasmonic applications and medical diagnosis. In order to ensure the optical functionality of these fibers, the diameter of the capillary hole needs to be realized with high accuracy. Here, we introduce a novel and noninvasive methodology to characterize optical fibers and discuss it for the assessment of capillaries. In this method, the fiber is side-illuminated by a coherent beam, and the resulting diffraction pattern is analyzed. This corresponds to an in-line holographic measurement in the presence of strong scattering. A numerical parameter retrieval allows us to characterize the capillary hole diameter with an accuracy of approximately 100 nm for radii between several hundreds of nanometers and several tens of micrometers.
CRIS-Team Scopus Importer:2023-04-20